Depression, Anxiety and Stress among Undergraduate Medical Students of a Medical College in Nepal: A Descriptive Cross-Sectional Study - Timsinha, Sidarth; Parajuli, Sudhir Raman (Nepal Journal of Health Sciences, 2023)
Introduction: Medical school has a stressful environment where students are confronted with significant academic, psychological and existential stressors that are often under-recognized and undertreated. The Medical education system has been improving in Nepal; however, only limited research has been conducted concerning the mental health status of medical students. Objective: To estimate the prevalence of depression, anxiety, and stress and their associated risk factors among medical students of a teaching hospital in Nepal. Methods: This was a descriptive cross-sectional online questionnaire-based survey conducted over a period of one month from September to October 2020 in the Department of Forensic Medicine at Manipal College of Medical Sciences (MCOMS), Pokhara, Nepal. The study included undergraduate students from the first to the fifth year. The sample was collected using a convenience sampling method. The Depression Anxiety and Stress Scale (DASS-21) was used as a tool to evaluate depression, anxiety, and stress among medical students. Results: The overall prevalence of depression, anxiety and stress among undergraduate medical students was 143(46.43 %), anxiety 180(58.44%) and stress 90(29.22%) respectively. Female students reported higher levels of depression 87(53.40%), anxiety104(63.80%) and stress 53(32.52%) than male students 56(38.60%),76(52.41%) and 37(25.52%) respectively. The major risk factors associated with depression, anxiety, and stress were a personal history of psychiatric illness and academic dissatisfaction. Conclusions: Depression, anxiety, and stress were all prevalent among undergraduate medical students. Understanding mental problems among medical students would help develop and incorporate student wellness programs to prevent the negative effects of poor mental health.